Łuciuk, Przyboś, Różewicz. Muzyka i poezja wobec niewyrażalności - Dobkowska, Renata (Investigationes Linguisticae, 2018)
The main purpose of this article is to characterize the concept of ineffability in the light of the art of poetry and song. Presented interpretations and analysis of two selected twentieth century songs composed by Julisz Łuciuk to the texts of Julian Przyboś and Tadeusz Różewicz are the practical supplement of theoretical contemplation of ineffability contained in the first part of this article.